Smoking may prevent pouchitis in patients with restorative proctocolectomy for ulcerative colitis. Issue 3 (March 1996) - Merrett, M N; Mortensen, N; Kettlewell, M; Jewell, D O
Abstract : Epidemiological studies have shown an increased risk of ulcerative colitis (UC) in non-smokers and particularly recent ex-smokers. Patients with UC have an increased risk of pouchitis following ileal pouch-anal anastomosis, which may be a manifestation of the original disease susceptibility. The aim of this study was to test the hypothesis that smoking habit may influence the incidence of pouchitis. All patients with a functioning pouch > or = 12 months at one centre were assessed. Patients were excluded if (a) the original indication was not UC (n = 5), (b) the excised pouch showed histology diagnostic of Crohn's disease (n = 2), and (c) data were inadequate (n = 4). Smoking data were collected by questionnaire, or direct interview, or both. Ex-smokers were those who had stopped smoking < 7 years before colectomy. Non-smokers included ex-smokers who had stopped > 7 years before colectomy. Pouchitis was defined as an increase in stool frequency > 8/day with acute inflammation on biopsy specimen histology. Each presentation requiring treatment was regarded as an episode. For comparison smoking habit was assessed with regard to three other adverse outcomes - haemorrhage, sepsis, and pouch excision. Of 72 non-smokers (mean follow up 3.5 years) 18 had 46 episodes of pouchitis. Of 12 ex-smokers (mean follow up 3.3 years) four patients have had 14 episodes of pouchitis. Only one smoker from 17 has had a single episode of pouchitis. This shows that smokers have significantly less episodes of pouchitis compared with non-smokers (p = 0.0005) and ex-smokers (p = 0.05). There was no association of smoking habit with other adverse outcomes.